A comprehensive electro-magneto-elastic buckling and bending analyses of three-layered doubly curved nanoshell, based on nonlocal three-dimensional theory. (1st February 2021) - Arefi, Mohammad; Amabili, Marco
Abstract: The present paper studies the three-dimensional magneto-electro-elastic bending and buckling analyses of three-layered doubly curved nanoshells based on nonlocal elasticity theory. The kinematic relations are developed based on two-variable sinusoidal transverse shear and thickness deformation theory. The transverse deflection is decomposed into bending, shear and thickness deformation components by using a two-variable sinusoidal shear deformation theory. The nanoshell is subjected to in-plane mechanical, electrical and magnetic loads in which these forces are accounted as external works in constitutive relations for buckling analysis. This introduces a variable transverse displacement along the thickness direction. The principle of virtual work is used to derive the governing equations of bending and buckling. Numerical results are obtained based on Navier's technique for simply-supported boundary conditions. A parametric analysis is performed to investigate the influence of the nonlocal parameter, the applied electric and magnetic potentials on the magneto-electro-elastic bending and buckling responses of doubly curved nanoshells.